Single-cell and transcriptomic analyses reveal the role of PCDH17 in the non-inflammatory tumor microenvironment of pancreatic cancer - Sun, Yong; Wan, Hong; Xiong, Jie; Cao, Kun; Yang, Dashuai; Huang, Jun (Frontiers in Endocrinology, 2025)
BackgroundThe PCDH17 family has emerged as a prominent research focus in the field of oncology; however, the precise mechanism underlying the regulatory role of PCDH17 in shaping the inflammatory tumor microenvironment in pancreatic cancer remains elusive.MethodA thorough examination was carried out to explore the presence of PCDH17 in cancerous tumor tissues and its association with genes related to inflammation. Additionally, we comprehensively examined the association between PCDH17 and immune cell infiltration as well as immunotherapy in pancreatic cancer. Moreover, the single-cell data of pancreatic cancer was utilized for analyzing PCDH17 expression, cell differentiation, and intercellular communication.ResultPCDH17 exhibited differential expression across various tumor types. The low-expression group of PCDH17 showed reduced levels of inflammatory genes. Immunoinfiltration analysis indicated a significant association between T-cell infiltration and the expression of PCDH17. Analysis of single-cell sequencing data revealed that PCDH17 was primarily expressed in endothelial cells, with a decrease in expression observed during cellular differentiation trajectory. Notably, inflammation-related genes also displayed significant changes in their expression patterns along the endothelial cell differentiation trajectory. Cellular communication investigations unveiled multiple signaling pathways through which endothelial cells interacted with T cells. The presence of PCDH17 in endothelial cells was verified through various immunofluorescence techniques, and a simultaneous decline in its levels was observed alongside the decrease in inflammatory factors within the tumor microenvironment.ConclusionThe predominant expression of PCDH17 was observed in endothelial cells, exhibiting a strong association with inflammatory genes and infiltration of immune cells. PCDH17 exhibits potential as a target for regulating the immune-suppressive tumor microenvironment in pancreatic cancer.